Water As We Know It - The Complexities of Sweden's VA Sector: From Shifts in Responsibility to PFAS Water Contamination - Karall,Josephine Signe (2025)
This thesis focuses on the communication of risks in the water sector in Sweden, centring on the 2013 PFAS water contamination scandal in Kallinge, Ronneby. Primarily, the water sector in Sweden lacks qualitative research stemming from the field of sociology, indicating how “wicked water problems” make it difficult to see who holds the responsibility in the sector when a crisis strikes. Herein, it is fundamental to investigate the narrative construction of how the sector is perceived by experts in the field and how risks are communicated. The main reason for the complexity of the water sector is because of how it is communicated publicly and managed internally. A Content Analysis of a variety of media material and interviews is used to understand the steep gap in communication between the water sector and the public, which contributes to the unawareness and disinterest in water stemming from the general public. Therein, one of the main findings indicates a lack of access points between the water sector and the public, which enhances the public's unawareness of risks such as PFAS, until a crisis gains their attention. In addition, when a crisis occurs as in the case of Kallinge it is contained as a local problem, adding to the public's unawareness of the dangers of PFAS. Finally, I introduce a new concept, the taken-for-granted fallacy, which is the key driver of the water sector’s complexity. It shows that trust, risk-taking and unawareness build upon one another in the water sector and keep the understanding for water as an amenity invisible. These findings highlight the urgency to create a United National Ministry for Water that oversees the work of all water-related municipalities in Sweden, to clarify the aims and contributions of the water sector. Last but not least, the thesis indicates a starting point to further deepen the understanding of the water sector from a qualitative perspective to enable more transparency and close the communication gap between the experts of the sector and the public.
Keywords: Risk; PFAS; Water Sector; Communication; Responsibility; Public Awareness; Water; Trust; Kallinge 2013; Water Scandal; Taken-For-Granted Fallacy